New insights into the molecular phylogeny and biogeographical history of Allium subgenus Melanocrommyum (Amaryllidaceae) based on plastome and nuclear sequences - Ibrokhimjon Ergashov; Ziyoviddin Yusupov; Alireza Dolatyari; Mina Khorasani; İsmail Eker; Nazgul Turdumatova; Georgy Lazkov; Farruhbek Rasulov; Hang Sun; Tao Deng; Komiljon Tojibaev (Plant Diversity, 2025)
Subgenus Melanocrommyum is the second largest subgenus of Allium, with a wide distribution ranging from the Canary Islands to northwestern India. This study investigates the phylogeny, biogeographic patterns, and morphological character evolution of the subgenus using 117 accessions representing 107 taxa across the 19 currently recognized sections within Allium subgenus Melanocrommyum. Although the subgenus is monophyletic, significant incongruence exists between morphological and molecular data. Our plastome-based phylogenetic analysis identified five distinct lineages (A–E), corresponding to the geographic distributions of the species. However, plastome lineages (A–E) and ITS clusters (A–G) were incongruent. Biogeographic and molecular dating analyses suggest that Melanocrommyum evolved in association with tectonic uplift events in Central Asia during the Late Miocene or Oligocene. Our finding that Melanocrommyum plastomes have lost infA and one copy rps19 gene indicate that the subgenus has undergone a relatively recent diversification. We also found that narrow leaves and fasciculate to semi-globose inflorescences may represent ancestral traits within the subgenus. This study provides new insights into the biogeographic history and trait evolution of Melanocrommyum, suggesting recent diversification influenced by tectonic events and climate change, while highlighting the complexity of molecular and morphological data integration.